Availability of CBCT and iatrogenic alveolar nerve injuries. (January 2013) - Suomalainen, Anni; Apajalahti, Satu; Vehmas, Tapio; Ventä, Irja
Abstract Objective. To examine whether the rapid increase in the availability of cone-beam computed tomography (CBCT) has changed the number of inferior alveolar nerve (IAN) injuries related to the removal of mandibular third molars in Finland. The hypothesis was that the number of nerve injuries should diminish due to better imaging methods. Materials and methods. The number of CBCT devices, the annual number of CBCT examinations and the number of permanent IAN injuries occurring between 1997 and 2007 were analyzed. The data was collected from three national registers: the Radiation and Nuclear Safety Authority, the Social Insurance Institution and the Patient Insurance Centre. A detailed analysis was made from the cases of permanent IAN injuries. Results. The first CBCT device was registered in 2002 and the cumulative number of these devices in 2009 was 22. There was an increase from 555 to 3160 in the number of annual CBCT examinations during the period 2004–2009. The total number of permanent IAN injuries during the years 1997–2007 was 129 and remained stable throughout the period (regression analysis, p = 0.974, r2 = 0.01). Conclusions. Contrary to this hypothesis, the availability of CBCT devices has had no significant influence on the number of IAN injuries related to mandibular third molar removals in Finland. More education should be given to optimize the use of CBCT to cover difficult cases that may give rise to complications.